The Role of the Dikmas Sub Unit of the Semarang Police Satlantas in Reducing the Number of Violations Perpetrated by Students During the Covid-19 Pandemic - Praja Pratama Justisia (Police Studies Review, 2021)
Indonesia as an archipelagic country with various religions, ethnicities and cultures certainly has high social vulnerability. During this Covid-19 pandemic, there are still many traffic violations committed by the community, especially students. The things that trigger the occurrence of these violations are due to internal factors such as selfishness and lack of concern for the environment as well as external factors such as lack of attention from parents and minimal education about ethics and traffic discipline. The focus of the research is how the role of the Semarang Polrestabes traffic education unit in reducing the number of traffic violations committed by students during the Covid-19 pandemic. This study was conducted to describe the role and factors that affect the performance of the Semarang Polrestabes Traffic Unit Dikmas Unit in reducing the number of traffic violations committed by students during the Covid-19 pandemic. As an analytical tool, the research uses Law No. 2 of 2002, Law No. 22 of 2009, the concept of roles, communication theory and management theory. The research approach is qualitative by obtaining empirical data at the Traffic Unit of the Semarang Polrestabes. The results showed that the management elements (personnel, budget support, infrastructure and methods used) related to the role of the Dikmas unit in reducing the number of traffic violations committed by students were still less intensive due to various factors, both internal and external. . The role of the Satlantas Dikmas Unit needs to be improved and carried out more intensively. In addition, the methods used in carrying out community education should then be made more straightforward and interesting, such as interesting posts on social media, webinars, and meetings through zoom meetings so that they can make the public, especially students, interested in the material presented.